Enhancing collaboration in BIM-based construction networks through organisational discontinuity theory: a case study of the new Royal Adelaide Hospital. (2nd September 2016) - Mignone, Gerard; Hosseini, M. Reza; Chileshe, Nicholas; Arashpour, Mehrdad
ABSTRACT: This paper discusses a case study of Australia's most technologically advanced health facility to address an identified gap in the body of the knowledge. That is, no comprehensive study has hitherto attempted to draw upon virtual team working theories to enhance collaboration in BIM-based construction networks (BbCNs). In response to this, the present study seeks to raise awareness of organisational discontinuity theory (ODT) as a recent theory for virtual teams, which enables BbCNs to embrace collaboration. To this end, the major challenges encountered and corresponding solutions adopted on a mega-project have been closely monitored and investigated. The study contributes to the field through the conceptualisation of typical barriers to collaboration in BbCNs from the perspective of ODT. Additionally, the discussions presented outline practical implications by demonstrating how the identified issues of collaboration in BbCNs could be effectively dealt with.